Zygnematophyceae (Streptophyta) da área de proteção ambiental Litoral Norte, Bahia, Brasil - Oliveira, Ivania Batista de (2011)
The work is a contribution to the knowledge of the phytoflórula of continental waters of the Environmental Protection Area Litoral Norte, located in the northern coastal plain of the State of Bahia. It deals with the floristic inventory of representatives of the class Zygnematophyceae, division Streptophyta. It was based on the analysis of 230 sample units collected during periods of drought (January to March 2009) and rain (June to August 2009). All sampled locations were georeferenced. We identified, described, illustrated and commented 527 taxa of zignemafíceas distributed in two orders, six families, 35 genera, 290 species, 209 varieties other than those typical of their respective species and 28 taxonomic forms equally non-typical, however, of their respective varieties. The presence of representatives of the order Zygnematales was registered for the first time for the state of Bahia, represented in this work by 18 taxa. Three hundred and three taxa from Desmidiales are being added to the ficoflórula of the state of Bahia and 98 taxa to that of Brazil. Nine taxa were identified only at the genus level, due to the absence of reproductive structures, which are absolutely essential for the taxonomy of species, varieties and taxonomic forms in Zygnemataceae. Twelve taxa are suggested as probable taxonomic novelties at the species level and seven at the variety level, the formal proposition of which will be made in due course, after a more accurate study and definition of the constancy, at the population level, of the diagnostic characteristics of each one. Qualitatively, the best represented genera were Cosmarium, Staurastrum and Euastrum with 128, 96 and 60 taxa, respectively, while the least representative were Bourellyodesmus, Cosmocladium, Docidium, Ichthyocercus, Phymatodocys, Sphaerozosma, Spirotaenia, Spinoclosterium, Triploceras and Zygnema, represented by a single taxon each. Forty taxa were registered only during the rainy season and only eight were exclusive to the dry season. Among the studied taxa, only eight were considered frequent while ca. 69% of them were classified as rare occurrence, as they are present in less than 10% of the total sample units analyzed. For each taxon studied, the following information was provided: (a) reference to the original description (work “princeps”); (b) basionym, when existing; (c) comparison with morphologically related taxa; (d) geographic distribution in the Brazilian territory; and (e) illustration. Finally, artificial dichotomous keys were presented to identify the families and genders inventoried in this study.